Soziale Arbeit - Kernthemen und Problemfelder. (Verlag Barbara Budrich, 2017)
The series "Social Work - Basics" provides a clear introduction to the subject. In volume 1, core topics and problem areas of social work are presented. Which topics are central to the specialist discourses of professional social work as well as to the scientific debate? How can they be integrated into Establishing relationships What criticisms, problems and challenges are associated with these terms?